2020
DOI: 10.22159/ijpps.2020v12i7.37703
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Rugged Bioanalytical Method Development and Validation of Brivudine in Human Plasma by Using High-Performance Liquid Chromatography

Abstract: Objective: The current research work focus to simple and rugged bioanalytical method development and validation of brivudine in human plasma using high-performance liquid chromatography. Methods: The analyte (Brivudine) and internal standard (Sofosbuvir) were extracted using the Solid Phase Extraction (SPE) technique. The chromatographic separation was accomplished by using Zorbax eclipse XDB-C18 Column (150×4.6 mm, 5 μm) with a mobile phase consisted of Methanol: 0.5% Ortho-phosphoric acid (65:3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Plasma sample's linearity was quantified using the peak-area ratio versus analyte nominal concentration [25]. For the establishment of the linearity range of the proposed method, calibration curves in plasma were prepared in the concentration range of 40-200 ng/ml.…”
Section: Linearitymentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma sample's linearity was quantified using the peak-area ratio versus analyte nominal concentration [25]. For the establishment of the linearity range of the proposed method, calibration curves in plasma were prepared in the concentration range of 40-200 ng/ml.…”
Section: Linearitymentioning
confidence: 99%
“…The ruggedness of the method was studied by changing the experimental condition with precision and accurate batch [25]. Ruggedness was performed by using different analysts [29] in the same laboratory.…”
Section: Ruggednessmentioning
confidence: 99%
“…The system suitability test of the chromatographic system was performed to confirm the adequate suitability and reproducibility of the system before each day of a validation run. A system suitability test was performed by injecting six consecutive injections using a standard aqueous mixture equivalent to middle concentration of the calibration standard curve of analyte and working concentration of ISTD [23].…”
Section: Validation Parameters System Suitabilitymentioning
confidence: 99%
“…This denotes that a compound is getting carried over from one injection to the next. The chromatographic system should be tested to evaluate the possibility of carry over by injecting mobile phase followed by an extracted blank, extracted lower limit of quantification (LLOQ), extracted ULOQ, and then once again extracted blank [22,23].…”
Section: Autosampler Carry Over Testmentioning
confidence: 99%
“…In addition, there are not enough methods that provide pharmacokinetic studies to be easily applicable for the determination of SLP in human plasma. Review of literature revealed that few methods were reported for the estimation of SLP including; spectrophotometric methods [5][6][7], gas chromatograhy [8] and chromatographic methods [9][10][11][12] in dosage form, in addition to, LC-MS/MS methods in plasma [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%